Wayang Sapuh Leger: Sarana Upacara Ruwatan di Bali - Wicaksana, I Dewa Ketut; Wicaksandita, I Dewa Ketut (Jurnal Penelitian Agama Hindu, 2023)
Until now, Balinese people believe that someone who is born in the wuku wayang should doing ruwatan sapuh leger. It is suspected that this belief manifests itself on the basis of mythology in literature, along with its practical meaning and function. This study aims to find out about Wayang Sapuh Leger and its sources Sang Mpu Leger as dalang ruwat, function and the meaning of Wayang Sapuh Leger. Qualitative analysis methods based on observation research, interviews and literature, are used in support of philological theory, the theory of princple of unity, and the theory of meaning to obtain research results. The results of the analysis concluded, the lukatan nyapuleger ceremony is a ceremony for purifying children born in the span of the tumpek wayang week. It is believed that this time is under the power of Bhatara Kala, and must be purified (lukat) through sesaji (banten) and holy water (tirta panglukatan/tirta sudamala), and first perform shadow puppets from a special story (the play Dewa Kala). The nyapuh-leger ceremony in Bali is thought to have originated from the manuscript of Tantu Panggelaran, in the XV or XVI centuries. When it is manifested, a puppeteer is called sang mpu leger in addition to being an artist: (a) the puppeteer as (the) communicator of the niskala realms (virtual world) and sekala (real world); (b) the puppeteers as (mpu) educators, instructors, and preachers; and (c) the puppeteers (sapuh leger) priests/philosophers and spiritualists. The function of Wayang Sapuh Leger for the life of the Balinese people is as a communication tool to strengthen beliefs, values, norms that live in society. Wayang Sapuh Leger as a form of sacred art has an important meaning and significance in the social order of the Balinese people, this is still believed and adhered to in the Balinese social structure.